Direct and Indirect Speech Acts in the Drama “A Streetcar named Desire” written by Tennessee William - Mahdi Ahmad; Z Zainurrahman (Program Studi Pendidikan Bahasa Inggris, STKIP Kie Raha Ternate, 2021)
A drama is a work filled with figurative languages ​​that are full of implied meanings. The purpose of writing a drama, of course, is to entertain the reader. However, a drama text can also be a source of pragmatic learning that is rich in expression. This research is one of pragmatic research on drama texts. Using content analysis techniques, the researchers attempted to portray the use of speech acts, both direct and indirect, used by Tennessee William in her play